Nanotubos óxidos aplicados a resinas compostas fotoativadas - Arruda, Larisa Baldo de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Titanium dioxide (TiO2) has been suggested as a promising material in several applications, especially those solar energy conversion, environmental applications, as photocatalysts, besides being used as biomaterial, mainly because it is a low-cost oxide, chemically stable and by present antibacterial properties. TiO2 nanostructures comes further increasing its field of application, especially when the size of the particles are smaller than 50 nm. The unique photoactivity of TiO2 nanoparticles and their superior mechanical properties when compared to its shape in bulk, makes it ideal as an additive to improve the performance of polymeric materials. In this work, TiO2 nanotubes and nanotubes of TiO2 with different cerium concentrations were obtained by alkaline synthesis followed by successive washes in acide and water, with different final pH values of the solution. The nanotubes obtained were morphologically and structurally characterized and then used as additives in a photopolymerized composite resin, at concentrations of 0.1, 0.3 and 0.6% by weight in order to improve the mechanical properties of hardness and elastic modulus of thet resin and increase the degree of conversion and thereby obtain an improved composite for dental applications. The results show that the show that the synthesized nanotubes, even of different chemical compositions, have an average diameter of 10 nm. It was possibe to identify two differnte growth types for these nanotubes, one from to sheets winding formed during the alkali treatment of starting material and other from to growth of TiO2 single crystals. The difference in final pH values synthesis shown to be an important factor for the determination of the crystal phase obtained, wherein pH values of 4 led to the formation of TiO2 anatase phase only, while pH values exceeding 7 favored the coesistence of TiO2 anatase phase and hydrogen titanate. When incorporated into the resin, the nanotubes acted as a...

O dióxido de titânio (TiO2) tem sido sugerido como um material promissor em diversas aplicações, destacando-se aquelas em conversão de energia solar, aplicações ambientais, como fotocatalizadores, além da utilização como biomaterial, principalmente por ser um óxido de baico custo, quimicamente estável e apresentar propriedades antibacterecidas. Nanoestruturas de TiO2 vêm ampliando ainda mais seu campo de aplicação, especialmente quando o tamanho das partículas são menores do que 50 nm. A fotoatividade única das nanopartículas de TiO2 e suas propriedades mecânicas superiores quando comparadas à sua forma em bulk, torna-as um dos aditivos ideais para melhorar o desempenho dos materiais poliméricos. Neste trabalho, nanotubos de TiO2 e TiO2 contendo diferentes concentrações de cério, foram obtidos por síntese alcalina seguida de sucessivas lavagens em meio ácido e água, com diferentes valores de pH final da solução. Os nanotubos obtidos foram caracterizados morfologicamente e estruturalmente e então utilizados como aditivos em uma resina composta fotoativada, nas concentrações de 0,1, 0,3 e 0,6% em peso, a fim de melhorar as propriedades mecânicas de dureza e módulo de elasticidade da resina, bem como aumentar o valor de grau de conversão e assim obter um compósito melhorado para aplicações odontológicas. Os resultados mostram que os nanotubos sintetizados, mesmo com diferentes composições químicas, apresentam diâmetro médio de 10 nm. Foi possível identificar duas formas de crescimento desses nanotubos, uma a partir do enrolamento de folhas, formadas durante o tratamento alcalino do material de partida, e outra a partir do crescimento de monocristais de TiO2. A diferença nos valores de pH final da síntese mostrou ser um fator importante para a determinação da fase cristalina obtida, em que valores de pH 4 levaram a formação exclusivamente da fase TiO2 anatase, enquanto valores de pH igual a 7...
Keywords: Nanotubos; Dióxido de titânio; Nanoestruturas; Sintese organica; Nanotubes